2020
DOI: 10.1038/s41598-020-59520-3
|View full text |Cite
|
Sign up to set email alerts
|

Mysterious long-living ultrahigh-pressure or secondary impact crisis

Abstract: High-pressure glass has attracted interest in terms of both its fundamental state under extreme conditions and its possible applications as an advanced material. in this context, natural impact glasses are of considerable interest because they are formed under ultrahigh-pressure and high-temperature (UHpHt) conditions in larger volumes than laboratory fabrication can produce. Studying the UHpHt glasses of the unique giant Kara astrobleme (Russia), we found that the specific geological position of the UHpHt mel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 48 publications
1
9
0
Order By: Relevance
“…Within the impact melt occurrences at the studied region of the Kara astrobleme, hydrothermal alteration generated smectite within their pore space, as observed by SEM (Shumilova et al, 2020). This smectite may not be related to autometasomatic alteration, but to general melt rock solidification with minerals formation during impact melt cooling -crystallization (Osinski et al, 2013).…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Within the impact melt occurrences at the studied region of the Kara astrobleme, hydrothermal alteration generated smectite within their pore space, as observed by SEM (Shumilova et al, 2020). This smectite may not be related to autometasomatic alteration, but to general melt rock solidification with minerals formation during impact melt cooling -crystallization (Osinski et al, 2013).…”
Section: Discussionmentioning
confidence: 78%
“…This smectite may not be related to autometasomatic alteration, but to general melt rock solidification with minerals formation during impact melt cooling -crystallization (Osinski et al, 2013). Shumilova et al (2020) proposed that the smectite that has been found within the ultrahigh-pressure high temperature impact melt vein glasses containing melt-crystallized singlecrystalline coesite (Shumilova et al, 2020). Origin of the smectite is beyond the scope of this paper.…”
Section: Discussionmentioning
confidence: 90%
“…UHPHT melt impact glasses were sampled in 2015 and 2017 from impactites of the southern sector of the Kara crater from vein bodies cutting suevite massif (Figure 1) at the Kara River (Pay-Khoy, Russia) and these are samples KP15-12-115 and KP15-12-118. A preliminary analysis of the structural state of these glasses was carried out using a set of standard mineralogical research methods [13,14,16]. The main feature distinguishing UHPHT melts from clast type glasses and massive melt impactites was found to be the multilevel differentiation of impact melt, including liquation of silicate and aluminosilicate melts and partial silica melt crystallization to UHP SiO 2 variety-monocrystalline coesite [13,14].…”
Section: Methodsmentioning
confidence: 99%
“…The discovery of a high concentration of non-bridging oxygen atoms was highly unexpected based on the results [17] used for the interpretation of Raman spectra. In addition, electron microscopic images presented in [13,16] showed the presence of widespread pyroxene (Q 2 ) microcrystallites in the glass matrix. These observations call for further investigation of the polymerization of the UHPHT impact Kara glasses.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation